(untitled) (Bangladesh Medical Journal, 2025)
Iron deficiency anaemia (IDA) remains a major public health concern among pregnant women in Bangladesh. Given the high prevalence of iron deficiency anaemia in pregnancy among Bangladeshi women injectable iron sucrose therapy during antenatal period may be effective in its treatment. The aim of this study was to evaluate the efficacy and safety of intravenous iron sucrose therapy in antenatal patients with IDA. A cross-sectional study was conducted among 150 pregnant women with mild to moderate IDA (Hb 7–9.9 g/dL, serum ferritin <12 µg/L) at Shaheed Suhrawardy Medical College Hospital from November 2017 to April 2018. Patients received calculated doses of intravenous iron sucrose. All of them received intravenous injection of iron sucrose in a calculated dose according to haemoglobin level. Haemoglobin levels were reassessed after 21 days of injection. Side effects were monitored. Approval of the study was obtained from Department of Obstetrics and Gynaecology, Shaheed Suhrawardy Medical College and Hospital. Written informed consents were obtained. Privacy and confidentiality of data were strictly maintained and preserved anonymously. Mean age was 26.09±5.39 years, 86% were housewife and about 9% were service holder; 58% were from lower socioeconomic condition; about 39% had secondary and higher level of education. Following three weeks of intravenous iron sucrose administration at the calculated therapeutic dose, mean haemoglobin levels rose by 2.35±0.53 g/dL, increasing from 7.52±0.43 g/dL at baseline to 10.88±0.43 g/dL post-treatment. The rise of the mean haemoglobin levels was statistically significant (p<0.001). Mild adverse effects were reported in approximately 13% of participants, including epigastric discomfort (4.7%), abdominal pain (3.3%), nausea and vomiting (2.7%), and allergic reactions (2%). No serious or major side effects were observed. Intravenous iron sucrose is a safe and effective therapy for IDA during pregnancy, with minimal side effects and significant improvement in haemoglobin levels. The administered dose should be calculated based on the patient’s body weight and the estimated iron deficit, as determined by haemoglobin concentration and serum ferritin levels. Bangladesh Med J. 2024 Sept; 53(3): 16-22